Pengamatan Pengendalian Berat Susu Kambing Etawa Bubuk Di CV TSR Menggunakan Metode Control Chart Dan Diagram Fishbone - Fahira Islami, Iasha; Nurindra Rahmadi, Safinta (Politeknik Negeri Ketapang, 2022)
CV TSR is one of the industries that produces Etawa goat's milk with some processing carried out manually, especially in the drying process when milk is mixed with sugar and heated in the traditional way, because it does not involve a heating process with a machine so there will be a possibility of uneven heat, skill differences between workers can also cause the rate of evaporation from one pan to another is different. Therefore, it is necessary to carry out heavy observations in order to guarantee product quality and minimize non-conformance to the SOPs that have been determined, especially in the process of receiving raw materials up to the production process. In analyzing the data, the methods used are control charts and fishbone diagrams. The results show that 5 data experienced out of control in observations for 15 days using the batch system and the results of the fishbone diagram that human factors greatly influence the discrepancy in the final results of powdered Etawa goat milk production so it is necessary to pay attention and disseminate knowledge of SOPs in handling fresh goat milk as the main raw material.